Effect of drying time rye used as cover crop on soil properties, weeds and yield of corn (Semiárida, 2018)
During the last decade, the Pampean Semarid Region showed an increase in cropping area by including soils of low aptitude which, in consequence, became degraded. Cover crops are a tool that can minimize such edaphic degradation and offset the carbon balance. This work's objective was to evaluate the effect of three drying dates (DD) of rye, as cover crop (CC), on water use efficiency (WUE) and biomass production of the CC, soil content of available water and nitrate, and the presence of weeds in and grain yield of a maize successor crop. The field trial was conducted at the Experimental Station INTA Anguil, La Pampa, and the DD assayed for the CC were july, august and september. Results showed that CC biomass production and WUE were higher for drying in August and September as compared to that done in july. Contents of available water and nitrate in the soil profile, as well as maize grain yield, were significantly reduced with the delay of CC drying. There was no difference in the amount of weeds present in maize crop among v6 and v8 phenological stages, and neither in maize grain yield, whether or not herbicides were applied. DOI: http://dx.doi.org/10.19137/semiarida.2016(01).11-18
Keywords: semiarid region; water use efficiency; weeds cover; soil water and nitrate